Tourism Impact on Conservation and Utilization of Borobudur Temple After Being Declared as Ten New Bali Tourist Destination in Indonesia - Cerry Surya Pradana; Carlos Iban; R. Setyastama (Journal of Indonesian Tourism and Development Studies, 2020)
Borobudur as a world heritage site is one of â€œ10 New Bali Tourist Destinationâ€ or â€œ10 Priority Tourist Destinationâ€ in Indonesia. The problem arises as governmentâ€™s aim to attract tourists as many as possible can be contrary to the conservation principles. This study aimed to identify the impact of the establishment of Borobudur Temple as one of 10 priority tourist destinations, specifically in terms of conservation and utilization. In addition, it is aimed to view the readiness and strategy of the manager of Borobudur Temple Heritage Site toward the policy of 10 New Bali Tourist Destination. The method used in this study is descriptive qualitative. Data will be collected by doing observation and in-depth interview as well as literature review. The data are analysed using the hermeneutic paradigm in which researchers expect the interpretations of the manager of Borobudur Temple Heritage Site dealing with the topic of the study. Data analysis is done by using hermeneutic paradigm which is expected to answer the research questions. The preliminary findings of this study, that are based on interview and literature review, state that there is a different job description between BKB and PT. TWCBRB. This study has found out the impact of the establishment of Borobudur Temple as 10 New Bali Tourist Destination in conservation and utilization term.Keywords: Borobudur Temple, heritagetourism, tourism impacts, 10 New Bali, 10 priority tourist destination.